Pour une phénoménologie de l'évidence esthétique. - Delmotte, Benjamin (Studia Phaenomenologica, 2017)
If the idea of a phenomenological aesthetic evidence is far from being obvious, it may yet become necessary in the description of the aesthetic experience. For the way a work of art can imperiously impose on the viewer reveals a kind of power that may suggests that this evidence is more than just a subjective feeling. Although Husserl's phenomenology doesn't consider such an evidence, and although this concept may even be regarded as a contradiction-- since evidence particularly characterizes the givenness of perceptive objects--we may yet find the conditions of possibility of such an aesthetic evidence in Husserl's work.